The Effect of Low Birth Weight on Stunting in Children Under Five: A Meta Analysis - Putri, Tyas Aisyah; Salsabilla, Dinda Anindita; Saputra, Rizki Kurniawan (Journal of Maternal and Child Health, 2021)
Background: The main nutritional problem in children under five, which is still found in many countries in the world, is stunting. The relationship between risk factors for low birth weight (LBW) in children has been investigated in several primary studies with a number of contradictions in the results. The purpose of this study was to determine the effect of low birth weight (LBW) on the incidence of stunting in children under 60 months in various countries using the meta-analysis method. Subjects and Method: The articles were selected from the Google Scholar, PubMed, Web of Science, Microsoft Academic, and Science Direct databases published from 2000-2021. Article collection for 2 months with search keywords (“Low Birth Weight” OR “LBW”) AND “Stunting” AND (“adjusted odds ratio” OR “multivariable”). The meta-analysis step used is a PRISMA flowchart. Data analysis was carried out using the Review Manager 5.3 . program. Results: Based on 11 primary studies conducted in Brazil, Ethiopia, and Indonesia, it was shown that in a cross-sectional study LBW could increase the incidence of stunting in children aged 0-60 months by 3.64 times compared to non-LBW (aOR = 3.64; 95% CI = 2.70). up to 4.90; p<0.001). While the case-control study showed that LBW can increase the incidence of stunting in children aged 0-60 months as much as 6.95 times compared to non-LBW (aOR = 6.95; 95% CI = 4.02 to 12.04; p<0.001). Conclusion: Low birth weight increases the risk of stunting in the population of children under 60 months of age.